P271 Evolving Targets in Ulcerative colitis: Defining Disease Clearance in the VARSITY Study. (27th May 2021) - Danese, S; Schreiber, S; Loftus, E; Colombel, J F; Peyrin-Biroulet, L; Agboton, C; Lindner, D; Lirio, R; Sands, B
Abstract: Background: In VARSITY, the first head-to-head randomized controlled trial of biologics, vedolizumab (VDZ) was superior vs adalimumab (ADA) in achieving clinical remission (CR) at Week 52 in patients (pts) with moderate to severe ulcerative colitis (UC). 1 Current treatment goals in UC are based on clinical symptoms and endoscopy, with histologic improvement considered an aspirational goal. 2-4 In pts with CR in VARSITY, greater treatment differences between VDZ and ADA at Week 52 were seen in endoscopic improvement and histologic response. Here, data from VARSITY were used to define disease clearance: a novel composite outcome in UC comprising clinical and endoscopic remission plus minimal histologic disease activity. Methods: VARSITY was a phase 3b, randomized, double-blind, double-dummy, active-control trial of treatment with VDZ (300mg IV Q8W) vs ADA (40mg SC Q2W) maintenance after induction. Pts were randomized in a treat through design, and no dose escalation was allowed. For these analyses, based on pts who completed the study until Week 52, disease clearance was defined as a composite outcome based on 1) CR: partial Mayo score ≤2 and no individual subscore >1 (excluding sigmoidoscopy subscore); 2) endoscopic improvement: endoscopic subscore ≤1; and 3) absence of active histologic disease (minimum histological disease activity [MHDA]): Robarts Histology Index (RHI) <5. Treatment failure was defined as discontinuation from treatment or completion of treatment but failure to achieve any of CR, endoscopic improvement, or MHDA. The rates of disease clearance and failures were compared between treatment groups and stratified by presence of inflammatory burden at baseline: C-reactive protein ≥5 mg/L and fecal calprotectin >100 µg/g. Results: More pts in the VDZ treatment group than the ADA group achieved disease clearance at Week 52 (VDZ: 112/383, 29.2%, 95% CI 24.7-34.1 vs ADA: 63/386, 16.3%, 95% CI 12.8-20.4). Compared with treatment failures (VDZ: 92/383, 24.0% vs ADA: 134/386, 34.7%, Table 1 ), disease clearers had lower C-reactive protein (CRP) baseline mean values (7.4mg/L and 6.4mg/L vs 13.6mg/L and 9.4mg/L for disease clearers vs treatment failures, for VDZ and ADA, respectively). Fewer pts with inflammatory burden at baseline (CRP ≥5 mg/L and fecal calprotectin >100 µg/g) achieved disease clearance (Fig 1 ). Baseline corticosteroid use was more frequent in ADA disease clearers (42.9%) compared with VDZ disease clearers (32.1%). Conclusion: Disease clearance is a novel and achievable composite outcome that is achieved by almost one third of pts in the VDZ treatment group in VARSITY. Analyses are ongoing to further characterize the trajectory leading to disease clearance as well as the role of baseline characteristics.